Identity Infrastructure Boost Concept for eduroam Service - Petrosyan, Arthur S.; Petrosyan, Gurgen S.; Tadevosyan, Robert N.; Arsalanian, Kevork Kh. (Изд-во НАН РА)
This paper presents the concept of authenticating eduroam users via their organization's IMAP server. The concept described is based on the fact that most organizations, even lacking their own personnel identity database, have at least an email service in place and, thus, have a working IMAP server for their organization domain name. Thus, the existing email username/password within a particular organization can be used as an identity source for eduroam authentication. The paper describes the components required to implement the concept, as well as some expected limitations for this solution. The concept is planned to be implemented in ASNET-AM network in order to stimulate more rapid use of eduroam service in Armenia. В статье представлена концепция ускоренного внедрения инфраструктуры eduroam в организациях. Описанная концепция основана на том факте, что даже если организации не имеют собственной базы данных идентификации персонала, они имеют по крайней мере службу электронной почты и, таким образом, имеют рабочий сервер IMAP для доменного имени своей организации. Таким образом, существующее имя пользователя/пароль электронной почты в конкретной организации может использоваться как источник идентификации для аутентификации eduroam. В статье описываются компоненты, необходимые для реализации концепции, а также некоторые ожидаемые ограничения и преимущества описанного решения. Концепцию планируется реализовать в сети ASNET-AM, для стимуляции ускоренного расширения использования услуги eduroam в Армении.
Keywords: Mathematical cybernetics; Computer science